Detection of human T cell lymphotropic virus type I proviral DNA and its gene expression in synovial cells in chronic inflammatory arthropathy. - Kitajima, I (1991)
To investigate the pathogenesis of human T cell lymphotropic virus type I (HTLV-I)-associated chronic inflammatory arthropathy (HAAP), we sought to detect proviral DNA in the articular lesions. For the detection of proviral DNA, we used the polymerase chain reaction (PCR). Proviral DNA was detected not only in the peripheral blood mononuclear cells (PBMCs) and synovial fluid cells (SFCs), but also in the T lymphocyte-depleted cultured synovial cells (CSCs). These findings suggest that the infection by HTLV-I might occur in vivo in non-T cells. Furthermore, we detected HTLV-I tax1/rex1 messenger RNA in fresh synovial tissues and CSCs but not in fresh PBMCs and fresh SFCs using reverse transcription and PCR. Immunohistochemically, the CSCs from HAAP patients were also shown to express the HTLV-I antigens. These data indicate that HTLV-I in the non-T synovial cells can be transcribed and expressed. Moreover, the sequences of pXII regions in the CSCs demonstrated 97.5-99.4% homology to that in MT-2 cells, HTLV-I-infected cell line. This confirmed that the PCR-amplified bands reflect HTLV-I itself. These results suggest that this organ-specific inflammation can be attributed to non-T cell virus infection in articular lesions.